Whole proteome analysis of post-translational modifications: Applications of mass-spectrometry for proteogenomic annotation - Gupta, Nitin; Tanner, Stephen; Jaitly, Navdeep; Adkins, Joshua N.; Lipton, Mary; Edwards, Robert; Romine, Margaret; Osterman, Andrei; Bafna, Vineet; Smith, Richard D.; Pevzner, Pavel A.

(untitled) (Genome Research, 2007)
While bacterial genome annotations have significantly improved in recent years, techniques for bacterial proteome annotation (including post-translational chemical modifications, signal peptides, proteolytic events, etc.) are still in their infancy. At the same time, the number of sequenced bacterial genomes is rising sharply, far outpacing our ability to validate the predicted genes, let alone annotate bacterial proteomes. In this study, we use tandem mass spectrometry (MS/MS) to annotate the proteome of Shewanella oneidensis MR-1, an important microbe for bioremediation. In particular, we provide the first comprehensive map of post-translational modifications in a bacterial genome, including a large number of chemical modifications, signal peptide cleavages, and cleavages of N-terminal methionine residues. We also detect multiple genes that were missed or assigned incorrect start positions by gene prediction programs, and suggest corrections to improve the gene annotation. This study demonstrates that complementing every genome sequencing project by an MS/MS project would significantly improve both genome and proteome annotations for a reasonable cost.